Levels, trends and impact of breast cancer mortality in Costa Rica by province, 2000–2009 - Agudelo Botero, Marcela (Población y Salud en Mesoamérica, 2011)
The aim of this study was to determine and analyze the levels, trends and impact of breast cancer mortality in Costa Rica by provinces, for the period 2000 to 2009. For this purpose was used the death records of Instituto Nacional de Estadística y Censos and other data (the female population projections and life tables, 2005), all available on the Centro Centroamericano de Población. Was a calculated crude rate and standardized mortality and estimated life years lost from breast cancer, all national and provincial level. Among the most important findings was that the standardized mortality rate from breast cancer increased 22% between 2000 and 2009 throughout the county, going from 21.3 to 26.1 per hundred thousand women. For the last year, Heredia had the highest mortality rate in the country (even above the overall average) and the lowest Cartago. In this period, both Limon as Cartago lowered their rates of mortality for this disease and all other provinces increased it. In Costa Rica, years of life lost from breast cancer in 2009 was 17 791, this indicator increased moderately compared to 2000 which was 15 490. These AVP in Costa Rica can be explained by demographic phenomena as women's reproductive changes and aging population as well as issues related to access and quality of health services.